Extremophilic Bacterium Halomonas desertis G11 as a Cell Factory for Poly-3-Hydroxybutyrate-co-3-Hydroxyvalerate Copolymer’s Production - Hammami, Khouloud; Souissi, Yasmine; Souii, Amal; Ouertani, Awatef; El-Hidri, Darine; Jabberi, Marwa; Chouchane, Habib; Mosbah, Amor; Masmoudi, Ahmed Slaheddine; Cherif, Ameur; Neifar, Mohamed (Frontiers in Bioengineering and Biotechnology, 2022)
Microbial polyhydroxyalkanoates (PHA) are biodegradable and biocompatible bio-based polyesters, which are used in various applications including packaging, medical and coating materials. In this study, an extremophilic hydrocarbonoclastic bacterium, previously isolated from saline sediment in the Tunisian desert, has been investigated for PHA production. The accumulation of intracellular PHA granules in Halomonas desertis G11 was detected by Nile blue A staining of the colonies. To achieve maximum PHA yield by the strain G11, the culture conditions were optimized through response surface methodology (RSM) employing a Box-Behnken Design (BBD) with three independent variables, namely, substrate concentration (1–5%), inoculum size (1–5%) and incubation time (5–15 days). Under optimized conditions, G11 strain produced 1.5 g/L (68% of DCW) of PHA using glycerol as a substrate. Application of NMR (1H and 13C) and FTIR spectroscopies showed that H. desertis accumulated PHA is a poly-3-hydroxybutyrate-co-3-hydroxyvalerate (PHBV). The genome analysis revealed the presence of typical structural genes involved in PHBV metabolism including phaA, phaB, phaC, phaP, phaZ, and phaR, coding for acetyl-CoA acetyltransferase, acetoacetyl-CoA reductase, class I polyhydroxyalkanoates synthases, phasin, polyhydroxyalkanoates depolymerase and polyhydroxyalkanoates synthesis repressor, respectively. Glycerol can be metabolized to 1) acetyl-CoA through the glycolysis pathway and subsequently converted to the 3HB monomer, and 2) to propionyl-CoA via the threonine biosynthetic pathway and subsequently converted to the 3HV monomer. In silico analysis of PhaC1 from H. desertis G11 indicated that this enzyme belongs to Class I PHA synthase family with a “lipase box”-like sequence (SYCVG). All these characteristics make the extremophilic bacterium H. desertis G11 a promising cell factory for the conversion of bio-renewable glycerol to high-value PHBV.